Racial Offenses Against the Sundanese Ethnic Group Reviewed from the Perspective of the Electronic Information and Transactions Law - Musa Darwin Pane; Khairunnisa Hanifati Zahra; Marta Ayuni Lestari Suhandi (Manunggal Halim Jaya, 2026)
This study aims to analyze the legal construction and law enforcement of racial offenses targeting the Sundanese ethnic group in the digital space based on the Electronic Information and Transactions Law (UU ITE). Using a normative legal research method with statutory, conceptual, and case approaches, this research focuses on the implementation of Article 28 paragraph (2) of the UU ITE. The findings indicate that the concept of racial offenses against the Sundanese ethnic group has been explicitly regulated with criminal sanctions of up to six years of imprisonment, as reflected in the case involving content creator R. in late 2025. However, law enforcement still faces challenges due to the ambiguity of the phrases